Measuring Constructive Journalism in Kompas.com’s Climate Change Articles - Levina Chrestella Theodora; Albertus Magnus Prestianta (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
Climate change poses a significant threat globally. Due to the heavy nature of the issue, climate change news tends to be very negative. Overly negative news can cause psychological disruption and make people avoid the news. The news media plays a huge role in climate mitigation, adaptation, and people’s perspectives on climate change, making it crucial for them to communicate climate change effectively. Constructive journalism may be the solution to this issue. With constructive journalism, journalists avoid negativity bias by focusing not only on the negatives but also on the solutions and positives when reporting a story. This study conducted a quantitative content analysis on 123 climate change articles reported by Kompas.com in 2020 using the six elements of constructive journalism. This research found that Kompas.com’s climate change articles in 2020 were not constructive. The articles emphasized the consequences of climate change with minimal constructive elements to balance the negativity.